1994
DOI: 10.1007/bf00293395
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis related antigen, LeY and nick-end labeling are positive in spinal motor neurons in amyotrophic lateral sclerosis

Abstract: Expression of Le(Y), a difucosylated type 2 chain determinant, has been previously identified as a characteristic of cells undergoing apoptosis. Immunohistochemistry using an antibody for Le(Y), as well as nick-end labeling for the detection of DNA breaks, was done on cervical spinal cord sections from ten patients with amyotrophic lateral sclerosis (ALS) and nine patients who had died from other causes. Le(Y)-positive immunoreactivity was seen in the motor neurons of seven ALS cases, but in none of the other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(11 citation statements)
references
References 13 publications
0
10
1
Order By: Relevance
“…If this is so, then motor neurons in ALS may be at a metabolic disadvantage given the observations of reduced levels of NFL steady-state mRNA in spinal motor neurons [17,18]. Although the consequences of reduced NFL protein might be predicted to be excessive levels of reactive nitrating species and potentially damage to key neuronal processes (e.g., DNA integrity leading to apoptosis), the evidence for apoptotis in ALS is scant [19][20][21]. Even in those neurons demonstrating ubiquitin immunoreactivity, we have found no evidence of apoptosis (He and Strong, current submission).…”
Section: Neuropathological Featuresmentioning
confidence: 99%
“…If this is so, then motor neurons in ALS may be at a metabolic disadvantage given the observations of reduced levels of NFL steady-state mRNA in spinal motor neurons [17,18]. Although the consequences of reduced NFL protein might be predicted to be excessive levels of reactive nitrating species and potentially damage to key neuronal processes (e.g., DNA integrity leading to apoptosis), the evidence for apoptotis in ALS is scant [19][20][21]. Even in those neurons demonstrating ubiquitin immunoreactivity, we have found no evidence of apoptosis (He and Strong, current submission).…”
Section: Neuropathological Featuresmentioning
confidence: 99%
“…Several studies have used nick‐end labelling to detect DNA fragmentation, indicative of apoptosis, in ALS. In one study on post‐mortem human tissue, nick‐end labelling was detected in motor neurones in the high cervical region in ALS cases but not at all in control cases which consisted of progressive supranuclear palsy, lacunar stroke, polyarteritis nodosa or non‐neurological conditions [140]. In two other studies, DNA fragmentation was detected by positive TUNEL staining in the motor cortex [37], brain stem [37], cervical cord [37], thoracic cord [37,85] and lumbar cord [37] of cases with ALS.…”
Section: Tunel/isel Stainingmentioning
confidence: 99%
“…These findings differ from the absence of apoptosis in all control specimens reported by Yoshiyama et al . [140]. Using TUNEL staining, Martin [80] detected internucleosomal DNA fragmentation in subsets of pyramidal neurones in the motor cortex, and cervical and lumbosacral spinal cord of ALS cases.…”
Section: Tunel/isel Stainingmentioning
confidence: 99%
“…It has been reported that apoptosis is upregulated during aging in various cells such as in Alzheimer's disease, amyotrophic lateral sclerosis, and Parkinson's disease. The number of DNA fragmented nuclei detected by terminal dUTP nick-end labeling (TUNEL) significantly increases in neurons located in frontal and hippocampal cortices, in spinal motor neurons, and in nigral dopaminergic neurons, [12][13][14][15][16] or in chronic inflammation (chronic hepatitis, chronic nephritis).…”
mentioning
confidence: 99%